ANALISIS KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 248/K/TUN/2008 PT.PELINDO I SEBAGAI PEMEGANG HAK PENGELOLAAN - RAFIQI RAFIQI (PREMISE LAW JURNAL, 2016)
Right to Manage is based on the Decree of the Agrarian Minister (now the Minister of Land and Spatial Plan) No. 9/1965. The HPL (Right to Manage Certificate) in the name of PT. Pelindo I (Persero) with area of ± 63,000 m2 was issued on March 3, 1993. The Supreme Court’s Ruling No. 246/K/TUN/2008 could be implemented by the issuance of the Directive of the Head of the National Land Agency of the Republic of Indonesia No. 3/2011 on the Management of Study and Handling Land Cases. The Verdict of the District Court in Article 54 states that BPN RI has to implement the court’s verdict which is final and conclusive. The obstacle of implementing the Supreme Court’s Ruling No. 248/K/TUN/2008 is that plaintiff does not file a request to the National Land Agency to revoke the HPL according to the Supreme Court’s Ruling No. 248/K/TUN/2008. The Panel of Judges in the Supreme Court’s Ruling No. 248/K/TUN/2008 handed down a Ruling that the HPL No. 1/Desa Belawan on March 3, 1993 in the name of PT. Pelindo I (Persero), especially on the land area of ± 63,000 m2, was legally null and void. Keywords: Analysis, PT. Pelindo I (Persero), Right to Manage